2023
DOI: 10.3390/antiox12030623
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Potential Mechanisms of Medicinal Mushrooms Antidepressant Activity: A Review

Abstract: Major Depression Disease is a common mental illness that affects more than 322 million people worldwide and it is one of the leading causes of mental and physical disability. The etiology of depression is a complex interplay of psychological, social, and biological factors. Currently, psychopharmacotherapy is based mainly on the monoamine theory, which states that depression is caused by an insufficient level of monoamines such as serotonin, norepinephrine, and/or dopamine. Due to the relatively low efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 215 publications
0
4
0
Order By: Relevance
“…Edible mushrooms contain precursors of serotonin; psilocybin is a natural psychedelic compound produced by various fungi species, which has shown beneficial effects for depression via anti-oxidant and anti-inflammatory effects, as well as by regulating neurogenesis, the gut–brain axis, and the expression of neurotrophic factors [ 172 ]. Interestingly, a clinical trial is currently investigating its role in depression for patients with PD (NCT04932434).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Edible mushrooms contain precursors of serotonin; psilocybin is a natural psychedelic compound produced by various fungi species, which has shown beneficial effects for depression via anti-oxidant and anti-inflammatory effects, as well as by regulating neurogenesis, the gut–brain axis, and the expression of neurotrophic factors [ 172 ]. Interestingly, a clinical trial is currently investigating its role in depression for patients with PD (NCT04932434).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Mushrooms have been found to consist of 57% carbohydrates (with 8% being dietary fiber), 4% fat, and 22% protein [1]. Many studies have demonstrated Foods 2024, 13, 1560 2 of 15 that many mushroom species exhibit distinct biological activities, including anticancer, antiproliferative, antioxidant, antibacterial, and DNA-protecting properties [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Natural chemicals obtained from mushrooms can be thoroughly investigated and evaluated, which can be extremely beneficial for treating both infectious and noninfectious disorders [ 7 , 8 ]. Medicinal mushrooms and fungi are believed to have 130 different therapeutic properties, including antiallergic [ 9 ], antiarthritic, antiasthmatic [ 10 ], anticancer [ 11 ], pesticide [ 12 ], antidepressive [ 13 ], antidermatophytic [ 14 ], antidiabetic [ 15 ], antifertility, antifungal [ 15 ], antihelminthic [ 16 ], cytotoxic [ 17 ], antihypercholesterolemic [ 18 ], antihyperlipidemic [ 19 ], antihypertensive [ 20 ], antihypocholesterolemic [ 21 ], anti-inflammatory [ 15 ], antimalarial [ 22 ], antimicrobial [ 15 ], antioxidant [ 11 ], antiparasitic [ 23 ], antispasmodic [ 24 ], antiviral [ 13 ], anticardiovascular illnesses [ 18 ], hepatoprotective [ 10 ], immunomodulator [ 22 ], immunostimulant [ 13 ], insecticidal [ 22 ], larvicidal [ 25 ], nematicide [ 26 ], nephroprotective, neuroprotective [ 13 ], osteoprotective [ 4 ], and vasodilator [ 27 ], among others.…”
Section: Introductionmentioning
confidence: 99%